Electrochemical Properties of Graphene Oxide Nanoribbons/Polypyrrole Nanocomposites - Johara Al Dream (C, 2019)
Graphene is a highly studied material due to its unique electrical, optical, and mechanical properties. Graphene is widely applied in the field of energy such as in batteries, supercapacitors, and solar cells. The properties of graphene can be further improved by making nanocomposites with conducting polymers. In this work, graphene oxide nanoribbons (GONRs) were synthesized by unzipping multiwall carbon nanotubes. Graphene nanoribbons were used to make nanocomposites with polypyrrole for energy storage applications. The synthesized nanocomposites were structurally and electrochemically characterized to understand their structure and electrochemical properties. The electrochemical characterizations of these nanocomposites were carried out using cyclic voltammetry. The specific capacitance of the nanocomposites was observed to decrease with increasing scan rates. The highest specific capacitance of 2066 F/g was observed using cyclic voltammetry for the optimized nanocomposite of GONR and polypyrrole. Our study suggests that the electrochemical properties of graphene or polypyrrole can be improved by making their composites and that they could be successfully used as electrode materials for energy storage applications. This study can also be extended to the self-assembly of other conducting polymers and graphene nanoribbons through a simple route for various other applications.